Satire et sociabilité au coeur de la pratique caricaturale de Lady Dalhousie (1786-1839) : vers une histoire des femmes caricaturistes britanniques - Ferron-Desautels, Marie (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2021)
In 1987, the archivist Marie Elwood published a paper discussing her research in Scotland, which led to the repatriation of Lord Dalhousie’s collection and the discovery of five caricatures painted by Lady Dalhousie during her Canadian sojourn from 1816 to 1828. Since then, nothing has been written on the subject matter, the humour, and the sociability that these caricatures involved, a lack this paper aims to fill. What was the target of Dalhousie’s satirical gaze? Was it common for an aristocratic woman such as Dalhousie to paint caricatures? In order to provide answers to these questions, I will examine the caricatural strategies employed by Lady Dalhousie as well as her satirical perspective. Finally, I will consider the sociability that surrounded the display of these images by relating Dalhousie to other British women who contributed to the creation and the circulation of caricatures during the eighteenth and nineteenth centuries.